The Effect of Age and Sex on Self-Esteem among Adolescent Students in Secondary Schools in Tanzania - Mauki, Chris Mungubariki; Marandu, Daniel (Papers in Education and Development, 2020)
This paper quantitatively assessed the effect of age and sex on self-esteem development among adolescent students in secondary schools in Kinondoni Municipality. The study employed correlation research design, using exclusively a structured questionnaire for data collection. 511 participants were involved in this study out of which 324 were from public secondary schools and 187 came from private secondary schools. Furthermore, multiple regression analysis was conducted to test the significant effect of age and sex on adolescents ' self-esteem. The Rosenberg Self-esteem scale, developed by Morris Rosenberg in 1965 was adopted for measuring levels of self-esteem. It was generally found that sex had a greater effect in self-esteem (p=.037<0.05) but age had no statistically significant effect on self-esteem (p=0.107>0.05). Keywords: adolescent, age, developmental patterns, secondary schools, self-esteem, sex.